Inflammatory mediators in nasal lavage among school-age children from urban and rural areas in São Paulo, Brazil - Galvão, Clóvis Eduardo Santos; Saldiva, Paulo Hilário Nascimento; Kalil Filho, Jorge Elias; Castro, Fábio Fernandes Morato (São Paulo Medical Journal, 2004)
CONTEXT: Some studies have shown that inflammatory processes in the nasal air passages may reflect or affect those in the lower airways. We decided to indirectly assess the inflammatory status of the nasal airways in two groups of children with different sensitization rates to aeroallergens. OBJECTIVE: To compare the inflammatory activity in the nasal airways, through the determination of mediators in nasal lavage fluid in two distinct populations. TYPE OF STUDY: Cross-sectional study. SETTING: Two public elementary schools, one in an urban setting and the other in a rural setting of the State of São Paulo, Brazil. METHODS: Two groups of 40 elementary school children with different sensitization rates to aeroallergens were formed. Samples of nasal lavage fluid were assessed for eosinophil cationic protein (ECP) and tryptase. Non-parametric tests were used for statistical analysis. RESULTS: Significantly higher levels of ECP were observed among students living in the urban area than those in the rural area (p < 0.05). No significant difference in the tryptase levels was observed. Also, the urban children who were sensitized to aeroallergens presented higher levels of ECP in nasal mucosa than the non-sensitized children, while this difference was not observed among the rural children. DISCUSSION: The lack of mast cell activity and increased eosinophil degranulation revealed a chronic inflammatory state in the nasal air passages. The higher eosinophil activity in the urban area, coinciding with higher sensitization to aeroallergens, suggests that there must be some factors in the urban area that can modulate airway inflammation by influencing the activation of inflammatory cells. CONCLUSION: Our findings showed that there was no difference in the concentrations of tryptase in nasal lavage fluids between the two studied groups. However, the children from the urban area presented with higher concentrations of eosinophil cationic protein than did those from the rural area. Also, the urban children who were sensitized to aeroallergens presented with greater concentrations of eosinophil cationic protein in nasal mucosa than the non-sensitized children, while this difference was not observed among the rural children.